Quality Of Remote Audits: Use Of Information Technology, Audit Evidence And Achievement Of Audit Objectives - Ana Amaliana; Yudhi Herliansyah (Journal of Social Research, 2024)
This study examines and analyzes the influence of the use of information technology and the adequacy of audit evidence on the quality of remote audits which have an impact on the achievement of audit objectives. The method/approach uses quantitative research methodswith statistical calculations of SEM PLS. The data source comes from primary data obtained through questionnaires. The sampling technique uses a purposive sampling technique, with the criteria of employee respondents with the position of Young Expert Examiner who has more than 10 years of experience in carrying out the examination, has led the inspection team and has had a working period in the AKN III work unit for more than 3 years. The results of the study show that theuse of information technology and the adequacy of audit evidence have a significant positive effect on the quality of remote audits and the achievement of audit objectives. This research provides benefits and suggestions for auditors to update their understanding and knowledge related to information technology and audit evidence conducted in remote audits. The originality/novelty of this study was carried out on respondents who met the sample criteria in the analysis unit of AKN III BPK RI which is a government external auditor institution that conducts audits of Ministries/Institutions.